2017
DOI: 10.1039/c7ra11792b
|View full text |Cite
|
Sign up to set email alerts
|

Highly luminescent silver nanocluster-doped fluorophosphate glasses for microfabrication of 3D waveguides

Abstract: Highly photoluminescent glasses were prepared by embedding silver nanoclusters (Ag NCs) in a fluorophosphate matrix using a melt-quenching method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
3
19
0
4
Order By: Relevance
“…A similar shift in the band gap due to the addition of Ag 2 O was also reported in [30]. The presence of silver nanoparticles is known to lead to an absorption band at ~400 nm, due to the surface plasmon resonance (SPR) of Ag NPs [2,7]. As shown in Figure 2a, no absorption band at ~400 nm can be seen indicating that Ag are dispersed in the network in a small size of Ag species.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…A similar shift in the band gap due to the addition of Ag 2 O was also reported in [30]. The presence of silver nanoparticles is known to lead to an absorption band at ~400 nm, due to the surface plasmon resonance (SPR) of Ag NPs [2,7]. As shown in Figure 2a, no absorption band at ~400 nm can be seen indicating that Ag are dispersed in the network in a small size of Ag species.…”
Section: Resultssupporting
confidence: 74%
“…Glasses have been of great interest for the development of various devices and optical components for photonics application due to their relatively easy manipulation. Glasses can be easily prepared in different shapes and sizes [2,3,4]. Among them, fluoro-phosphate-based glasses are considered as a prospective candidate due to their excellent transparency, low phonon energy, good mechanical and chemical stability, low melting point, and high ability to incorporate a large amount of rare earth dopants compared to silicate glasses, due to their two dimensional structure [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoluminescence spectrum of the AgNCs/CMC nanocomposite film in Figure 4b shows a distinct emission peak around 550 nm at excitation of 365 nm, which is assigned to the typical photoluminescence feature of AgNCs. [ 56,68 ] Again, there is no emission peak in the photoluminescence spectrum of the control CMC sample. The inset in Figure 4b reveals that the solution containing AgNCs exhibits a clear yellow fluorescence under 365 nm UV light, whereas the control CMC solution shows no fluorescence (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, silver-containing fluorophosphate glasses have gained very limited attention with respect to DLW. Recently, Fares et al have demonstrated the feasibility of Ag NC's doped fluorophosphate glasses for waveguide inscription, operating a Ti:Saphire laser at 800 nm [26]. Besides, thanks to the low viscosity allowed by the phosphate groups, these vitreous systems own a large metal solubility.…”
Section: Introductionmentioning
confidence: 99%